ANALISIS KORELASI PRECIPITABLE WATER VAPOR (PWV) DARI DATA GNSS DENGAN CURAH HUJAN DI INDONESIA - Barbarosa, Azhari
GNSS (Global Navigation Satellite Systems) has become a part of society in their activities, such as in navigation, construction projects, deformation measurement, and much more. GNSS is a positioning system with the help of a constellation of satellites that can provide position information anytime, anywhere, and in any weather conditions. However, GNSS can also estimate Precipitable Vapor Vapor (PWV). PWV is water vapor in the atmosphere that will become dew and fall into rain. In this topic, the researcher aims to analyze the correlation between PWV and rainfall in Indonesia. The methodology used is research planning, literature study, searching and collecting data, processing data, presenting data, analyzing results, as well as conclusions and suggestions. The data used are observation data from InaCORS stations on the islands of Sumatra, Java, Kalimantan, Sulawesi, and areas of Eastern Indonesia and Papua Island as well as rainfall data that occurred at the InaCORS station during 2019. These data are normalized every five days (pentad days) and compared to each other. The statistical calculation used to determine the existing correlation is the calculation of the correlation coefficient. The resulting product is a comparison model in the form of graphs and plots of the distribution between pentad days PWV data and rainfall. For Sumatra Island, the correlation coefficient values for CSAB, CBKT, and CMEN stations are 0.49901, 0.53156, and 0.64985. For Java, the correlation coefficient values for CLBG, CJPR, CPAC, CMJT, and CMAT stations are 0.75047, 0.599, 0.6456, 0.65322, and 0.67128. For Kalimantan Island, the correlation coefficient values for CBAS, CBJM, and CBAL stations are 0.3795, 0.54133, and 0.51522. For Sulawesi Island, the correlation coefficient values for CMAK and CBIT stations are 0.61186 and 0.59358, respectively. For Eastern Indonesia and Papua Island, the correlation coefficient values for CTER, CSOQ, CJYP, CWMN, and CUKE stations are 0.64687, 0.54521, 0.25352, 0.46827, and 0.54521. The positive correlation coefficient value indicates that the PWV derived from the GNSS data is directly proportional to the rainfall that occurs in Indonesia.